Operational Management For “Mining Contractors Services Company” In Indonesia - Andrea Sigit Sulaksono; Rhian Indradewa (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Background - The mining contractor services business that Company will operate focuses on the process of mining overburden material and coal mining products which are carried out in an open pit manner, then the coal products will be hauled or transported to the port of the concession owner. This operational process requires operational costs in accordance with the work according to the contract, Operational costs are very influential in getting a positive profit margin, because this business is what the client or concession owner pays is the rate of /BCM of Overburden and /Ton of coal produced. The Company only gets service revenue, not the selling price of the coal. This makes the operational cost factor very significant in maintaining this mining service business costs are very influential in getting a positive profit margin, because this business is what the client or concession owner pays is the rate of /BCM of Overburden and /Ton of Coal produced. The Company only gets service revenue, not the selling price of the coal. This makes the operational cost factor very significant in maintaining this mining service business.